Status of Outpatient Department based Teaching-learning in Undergraduate Medical Education of Bangladesh (Bangladesh Journal of Medical Education, 2023)
Background: Disease burden of the society is reflected in Outpatient Departments (OPDs). The doctor-patient interaction mostly occurs in OPD and it offers many unique learning opportunities to the undergraduate medical students. Most of the knowledge, skill and attitude require for professional practice can be learnt in an OPD setting.Objectives: This study was driven to explore the current status of OPD based teaching-learning in undergraduate medical education of Bangladesh.Materials and Methods: This was a descriptive type of cross sectional study conducted in selected eight medial colleges of Bangladesh from January to December 2022.Total sample size was 430; out of which 207 were students, 205 were teachers and Key Informants were 18. The data were collected by two sets of pre-tested questionnaires, interview schedule and checklist.Result: out of 205 teachers 84(41%) were from govt. medical colleges and 121(59%) were from non-govt medical colleges and 125(61%) teachers had more than 10 year of teaching experience. Out of 207 students,162 (78.3%) were female and 45(21.7%) were male. The study revealed 178(89%) of teachers and 183(88.4%) of students faced challenges during OPD class. Administrative problems were identified by 110(53.7%) teachers and 115(55.56%) students and rest of the participants stated academic problems. Special OPD setup was suggested by 156(76.1%) teachers and 189(91.3%) students. The study also revealed that 15(83.3%) key informants suggested in favour of reviewing undergraduate medical curriculum regarding similar class duration with in-patient department and OPD placement.Conclusion: The study concluded that undergraduate medical curriculum is to be reviewed with special emphasis on OPD based teaching-learning regarding duration, phases of placement and special OPD set up for maximum utilization of precious OPD time.Bangladesh Journal of Medical Education Vol.14(2) July 2023: 18-22